Bridging indigenous knowledge and science learning through the tutulena traditional game: A qualitative study - Ni Nyoman Rediani; Pande Made Dharma Sanjaya; Yustri (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
Traditional games are part of indigenous knowledge that has the potential to be a source of contextual learning; however, their use in learning Natural and Social Sciences (IPAS) remains limited. This study aims to explore the ethnoscience dimensions contained in the traditional game of Tutulena and analyze its relevance to science learning in elementary schools. The research used a qualitative approach with an ethnographic design involving 18 informants, consisting of traditional figures, cultural actors, elementary school teachers, the community, and students. Data were collected through participatory observation, in-depth interviews, documentation, and field notes, then analyzed using an interactive analysis model that includes data condensation, data presentation, and drawing and verifying conclusions. The results of the study indicate that the Tutulena game contains local knowledge that is reflected in the process of selecting materials, making tools, implementing the game, and using natural resources sustainably. The ethnoscience dimensions found include the concepts of plant diversity, material properties, elasticity, force, motion, energy changes, and ecosystems that are relevant to the learning outcomes of science and natural sciences. This study concludes that the Tutulena game has the potential to be an ethnoscience-based learning resource that connects local knowledge with scientific concepts, thus supporting contextual, meaningful, and culturally preservation-oriented science and natural science learning. It is recommended that educators integrate Tutulena and other indigenous traditional games into science learning and that future studies examine their effectiveness in improving students' conceptual understanding, critical thinking skills, and appreciation of local cultural heritage.